Understanding mobile digital worlds: how do Australian adolescents relate to mobile technology?. Issue 4 (8th August 2018) - Ng, Wan; Nicholas, Howard
ABSTRACT: Various responses to the ideas of a digital disconnect between home and school include the call for a more thoughtful exploration of the relationship between formal and informal uses of technologies. Studies have indicated the complex and interacting influences on patterns of technology use at home and at school, including patterns of Web 2.0 use that do not align with common assumptions about the characteristics of current students. Together, these studies indicate that we need more nuanced insights into how today's students relate to available digital technologies if we are to build appropriately on their experiences in education. The current research investigates quantitatively mobile digital practices and literacy as well as attitudes in over 1140 school students in the first years (7–10) of secondary education in Australia in order to enrich insights into these students as learners in contemporary classrooms. The implications of the research for teaching are discussed.